Rising and falling diphthongs in Romance languages: A study of the phonological string - Savoia, Leonardo M.; Baldi, Benedetta (LingBaW. Linguistics Beyond and Within, 2024)
This article discusses the phonological status of diphthongs and their role in the melodic and rhythmic organization of vowel and consonant sequences. We examine the nature of rising diphthongs and their distribution in relation to syllabic structure. Structural approaches, such as GP, admit only falling diphthongs, insofar as only these respect the governing relation within the nucleus or rhyme, which requires the head to be on the left. However, rising diphthongs are widespread in languages and are subject to similar distributional constraints as falling diphthongs. The latter, in turn, also show realizations different from those generally considered canonical in the literature, such as English [ai] of my. Furthermore, not only rising but also falling diphthongs can occur in closed syllables. We argue for a model capable of unifying the treatment of diphthongs, aiming to achieve at least a descriptive adequacy. We adopt a CVCV approach, which aims to account for the organization of phonetic sequences and the licensing relations between vowels (and consonants) based on the melodic strength of the vowels.